A simulation interface designed for improved user interaction and learning in water quality modelling software. (August 2015) - Moeseneder, Christian; Dutra, Leo; Thebaud, Olivier; Ellis, Nick; Boschetti, Fabio; Tickell, Sharon; Dichmont, Cathy; de la Mare, William; Pascual, Ricardo; Cannard, Toni
Abstract: Traditional simulation software that supports management decisions is configured and run by experienced scientists. However, it is often criticised for its lack of interactivity, not only in the application of decisions but also in the display of results. This paper presents the simulation interface of software with management strategy evaluation capabilities and its capacity to enable resource managers to learn about water quality management as evaluated in a workshop setting. The software 'MSE Tool' is not intended to produce definitive real-world advice but provides a test-bed for managers to interactively design strategies and explore the complexities inherent to water quality management using a simple, yet effective, user interface. MSE Tool has been used in a pilot application that simulated the effects of management strategies applied in catchments and their effects on riverine, estuarine and marine water quality in South East Queensland, Australia. The approach and the software are suitable for reuse in other management strategy evaluation projects. Highlights: We present a reusable interface for management strategy evaluation software. We place the software in the context of water quality management in South East Queensland, Australia. We discuss the importance and benefits of interactivity in simulation software. We discuss differences between real-world decision support software and software that allows exploration of scenarios. We present results from user workshops which show an improvement in learning to use our simulation software.